The transmedia storytelling applied to corporate communication - Mut Camacho, Magdalena (2019)
The continuous changes in social, technological and media dynamics have forced the communication strategies of companies to constantly change. In the current context, characterized by low attention rates, the saturation of messages and multi-screen consumption, content has become a distinctive and valuable element to connect with audiences. In this sense, the transmedia storytelling, offer characteristics that encourage the participation and involvement of the audiences to which they are directed. This research intends to make a bibliographical review to discover what the key elements of this storytelling are. The ultimate goal will be to analyze its potential for its application to communication in organizations. As a first approximation, it is worth noting that although the transmedia storytelling complies with the basic principles of relation with the public, its use will be of no value to the organizations if the stated objectives are not aligned with the strategic approaches of corporate communication.